2007
DOI: 10.1159/000099472
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver Burden Associated with Behavioral and Psychological Symptoms of Dementia in Elderly People in the Local Community

Abstract: Background: Despite many studies about the association between caregiver burden and behavioral and psychological symptoms of dementia (BPSD), there have been no population-based studies to evaluate caregiver burden associated with each BPSD. Objective: To evaluate caregiver burden associated with the individual BPSD in elderly people living in the community. Methods: The subjects were 67 participants with dementia living with their caregivers (diagnosed in the third Nakayama study): 51 Alzheimer’s disease, 5 v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
130
3
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(146 citation statements)
references
References 37 publications
10
130
3
1
Order By: Relevance
“…Dementia-related impairments [8,9,10] of care recipients (CR) including cognitive and physical impairments as well as behavioral and psychological symptoms of dementia (BPSD) [12,13] and the social support for caregivers [14] are two external factors that have been reported to be strong predictors of HRQoL. The impairments of CR, particularly BPSD that can increase caregiver burden [6,9,10,15,16,17], were found to be detrimental to caregivers' HRQoL [9,18]. Social support has been regarded as an influential buffer in dealing with the stressful task of caring for a family member with dementia [19].…”
Section: Introductionmentioning
confidence: 99%
“…Dementia-related impairments [8,9,10] of care recipients (CR) including cognitive and physical impairments as well as behavioral and psychological symptoms of dementia (BPSD) [12,13] and the social support for caregivers [14] are two external factors that have been reported to be strong predictors of HRQoL. The impairments of CR, particularly BPSD that can increase caregiver burden [6,9,10,15,16,17], were found to be detrimental to caregivers' HRQoL [9,18]. Social support has been regarded as an influential buffer in dealing with the stressful task of caring for a family member with dementia [19].…”
Section: Introductionmentioning
confidence: 99%
“…These BPSD occur in a dynamic process involving the patient, the family caregiver and their environment. They are known to be more stressful to caregivers than cognitive or functional decline, because are felt as the most difficult to manage (Donaldson et al, 1998;Hooker et al, 2002;Vugt et al, 2003;Matsumoto et al, 2007) and have a negative impact on the relationships between the caregiver, patient and family (Lyons et al, 2002). It has been reported that caregivers differ in their emotional responses to BPSD even when facing similar problems and the caregiver's perception of patient's problems is more important than problem behaviour 'per se' (Zarit, 1996;Vugt et al, 2005), furthermore, caregivers can interpret poorly and react inadequately to BPSD (Paton et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of etiology, behavioral symptoms are challenging for family caregivers and result in considerable consequences including caregiver burden and stress [13,14] increased risk for placement [15][16][17] and significant cost to the health care system [18,19]. Some data report that caregivers of people with FTD and dementia with Lewy bodies (DLB) are particularly burdened by behavioral symptoms [20,21].…”
Section: Introductionmentioning
confidence: 99%